End-to-end Performance Isolation through Virtual Datacenters - Angel, Sebastian; Ballani, Hitesh; Karagiannis, Thomas; O'Shea, Greg; Thereska, Eno and (OSDI'14: The 11th USENIX Symposium on Operating Systems Design and Implementation, 2014)
The lack of performance isolation in multi-tenant datacenters at appliances like middleboxes and storage servers results in volatile application performance. To insulate tenants, we propose giving them the abstraction of a dedicated virtual datacenter (VDC). VDCs encapsulate end-to-end throughput guarantees—specified in a new metric based on virtual request cost—that hold across distributed appliances and the intervening network. We present Pulsar, a system that offers tenants their own VDCs. Pulsar comprises a logically centralized controller that uses new mechanisms to estimate tenants' demands and appliance capacities, and allocates datacenter resources based on flexible policies. These allocations are enforced at end-host hypervisors through multi-resource token buckets that ensure tenants with changing workloads cannot affect others. Pulsar's design does not require changes to applications, guest OSes, or appliances. Through a prototype deployed across 113 VMs, three appliances, and a 40 Gbps network, we show that Pulsar enforces tenants' VDCs while imposing overheads of less than 2% at the data and control plane.